Ilustraciones de los personajes de la fiesta popular de la Mama Negra para promover la identidad cultural en la juventud Latacungeña. - Llumiquinga Catota, Cristian David (2018)
The Popular Festival, “Mama Negra”, has become in one of the most traditional traits of Latacunga city. Through the time it has remained, and today is considered as intangible heritage of the nation. Keeping in mind that youngers are important to boost their cultural identity and their relationship with sports. Those factors provide opportunities for social interaction and the necessary attitudes for their full participation in the society. By not improving the levels of visibility the rest of the year and the limited contribution of textile clothing which one generates value and cultural identity in youth people from Latacunga. It is proposed to raise these indicators by means of illustrations of the main characters of this popular festival. Using saturated pop art as an artistic vanguard is possible, it has become an innovative way at the moment of offering a product or service. Through field investigation techniques such as survey, interview and bibliography. Furthermore, it was identified and characterized theoretical and visual information to be applied in the basic design through the Bruno Munari procedure. He stablished the following process as: problems’ definition, problems’ elements, data collection, creativity, materials and technologies. The experimentation and models will be unified to establish the proposal of youth textile clothing in support of improving levels of visibility. It generates greater interest in meeting other characters that constitute this popular festival.